SLC39A8 Deficiency: A Disorder of Manganese Transport and Glycosylation - Park, Julien H.; Hogrebe, Max; Grüneberg, Marianne; DuChesne, Ingrid; von der Heiden, Ava L.; Reunert, Janine; Schlingmann, Karl P.; Boycott, Kym M.; Beaulieu, Chandree L.; Mhanni, Aziz A.; Innes, A. Micheil; Hörtnagel, Konstanze; et al. (American journal of human genetics, 2015)
SLC39A8 is a membrane transporter responsible for manganese uptake into the cell. Via whole-exome sequencing, we studied a child that presented with cranial asymmetry, severe infantile spasms with hypsarrhythmia, and dysproportionate dwarfism. Analysis of transferrin glycosylation revealed severe dysglycosylation corresponding to a type II congenital disorder of glycosylation (CDG) and the blood manganese levels were below the detection limit. The variants c.112G>C (p.Gly38Arg) and c.1019T>A (p.Ile340Asn) were identified in SLC39A8. A second individual with the variants c.97G>A (p.Val33Met) and c.1004G>C (p.Ser335Thr) on the paternal allele and c.610G>T (p.Gly204Cys) on the maternal allele was identified among a group of unresolved case subjects with CDG. These data demonstrate that variants in SLC39A8 impair the function of manganese-dependent enzymes, most notably β-1,4-galactosyltransferase, a Golgi enzyme essential for biosynthesis of the carbohydrate part of glycoproteins. Impaired galactosylation leads to a severe disorder with deformed skull, severe seizures, short limbs, profound psychomotor retardation, and hearing loss. Oral galactose supplementation is a treatment option and results in complete normalization of glycosylation. SLC39A8 deficiency links a trace element deficiency with inherited glycosylation disorders.